The Oxford-Durham study: a randomized controlled trial of dietary supplementation with fatty acids in children with developmental coordination disorder (American Academy of Pediatrics, 2005)
Background: Developmental coordination disorder (DCD) affects around 5% of school age children. In addition to the core deficits in motor function, this condition is commonly associated with difficulties in learning, behavior and psychosocial adjustment that persist into adulthood. Mounting evidence suggests that a relative lack of certain polyunsaturated fatty acids may contribute to related neurodevelopmental and psychiatric disorders such as dyslexia and AD/HD. Given the current lack of effective evidence-based treatment options for DCD, the use of fatty acid supplements merits investigation. Methods: A randomized controlled trial of dietary supplementation with omega-3 and omega-6 fatty acids versus placebo was conducted in 117 children with DCD aged 5-12 years. Treatment for 3 months in parallel groups was followed by a one-way crossover from placebo to active treatment for a further 3 months. Results: No effect of treatment on motor skills was apparent, but significant improvements for active treatment versus placebo were found in reading, spelling and behavior over 3 months of treatment in parallel groups (p< 0.01 in each case). Following the crossover, similar changes were seen in the placebo-active group, while children continuing with active treatment maintained or improved their progress. Conclusions: Fatty acid supplementation may offer a safe and efficacious treatment option for educational and behavioral problems in children with DCD. Further work is needed to investigate whether our inability to detect any improvement in motor skills reflects the measures used; and to assess the durability of treatment effects on behavior and academic progress.